Evaluation of the Fertility Status of Rice Fields in Giri Jaya Village, Nagrak District, Sukabumi Regency - Rahmayuni, Erlina (Departemen Ilmu Tanah dan Sumberdaya Lahan, Fakultas Pertanian Universitas Andalas, 2024)
Rice field management plays a crucial role in successfully increasing rice production. This research aims to assess the fertility status of rice fields situated at varying altitudes in Giri Village, Nagrak District, Sukabumi Regency. The research comprises three stages, which include: Field research, Laboratory research, encompassing the analysis of soil chemical properties. Data analysis, conducted both descriptively and quantitatively. Composite soil samples from rice fields were collected at three different elevations (top, middle, and bottom) at a depth of 1-20 cm in the surface layer of the rice field soil. Analysis of paddy soil samples involved measuring pH H2O using the electrometric method, total N, and cation exchange capacity (CEC) using the titrimetric method, potential K2O using the flame photometric method, potential P2O5 and organic C using the spectrophotometric method, K-dd and Na-dd using the flame photometric method, and Ca-dd and Mg-dd using the AAS method. Data obtained from soil analysis at different elevations were compared based on soil type for each observed parameter. The research results indicate that the evaluation of nutrient status is influenced by altitude. Land situated at lower elevations exhibits better soil fertility status, followed by land at the upper and middle elevations.Â Keywords: Altitude, Andisols, Erosion, Rice fields, Soil fertility.